Speech by the Honourable Chief Minister, Penang, at the Launching of Rukun Tetangga Post , Cecil Street, on Sunday, 18th, July 1976 at 10.30 a.m - Lim, Chong Eu (1976)
I would like to thank the Committee Members of the Bridge Street Rukun Tetangga Sector II for having successfully organised themselves to implement the scheme in their sector.